The Urgency of Village Fund Management Planning - Kuahaty, Sarah Selfinah; Pesulima, Theresia Louize; Sinaga, Roulinta Yesvery (Batulis Civil Law Review, 2023)
Introduction: The development of Indonesia is an ongoing program established by the government, which is not solely focused on urban development but is currently prioritized starting from rural areas. Purposes of the Research: To achieve this goal, the government has allocated state finances in the form of village funds. One form of village fund management is village expenditure, the implementation of which must comply with the Minister of Finance Regulation Number 201/PMK.07/2022 concerning Village Fund Management.Methods of the Research: This paper was produced by conducting research using normative legal research methods.Results of the Research: The West Seram Regency government recently inaugurated village heads within its jurisdiction since 2022, in several waves, following earlier controversies regarding the determination of village and traditional villages' status. During this period, many villages were led by officials acting as village heads (caretakers), including Sanahu village, the location of this research, whose village head will only be appointed at the end of 2022. Village development planning is the initial step in village fund management, formulated in the Musrembangdes, which consists of the Village Consultative Body (BPD) and community representatives to prepare the Village Medium-Term Development Plan (RPJM Desa) and the Village Annual Work Plan (RKP) for the year 2022, which will be realized in 2023. During the implementation of the work programs, it was observed that some programs could not be carried out because they did not align with the village head's vision and mission, as they were merely copied from other villages' programs. This, of course, significantly affects the absorption of village funds.